INDUCTION OF CHROMOSOMAL POLYPLOIDY AND EARLY EVALUATION OF Ceratonia siliqua L. - N. Th. Saieed (Mesopotamia Journal of Agriculture)
This study was conducted at Forestry Department for the period 1st February until the end of November 2007 . to achieve chromosomal polyploidy in Ceratonia siliqua L. by soacking their seeds in different Colchicine solution concentration Zero . 500 . 1000 . 2000 ml / l . and different periods 6 . 12 . 18 . 24 hr . The treated seeds with different colchicine concentration mentioned above were Sown in plastic bag polly ethelen containing Sandy loam soil . Other seed lots treated with colchicine were placed in incubator after sowing them in Petri – dishes to count seed germination percentages followed by chromosome counts in root apices as following : Colchicine concentration effect :The results showe a tetraploidy level 4n = 48 chromosome when seeds soacks in 2000 mlg / l concentration of colchicine solution pre – sowing with Ratio of 44.96 % . but for 1000 mlg / l conc. of colchicine the mean ratio of tetraploidy level was 20.21 % . while tetraploidy was not noticed for other treatments which was diploid 2n=24 . traits studied the 2000 mlg / l caused a significant increases 13.7 % for germination ratio . 40.96 % for Shoot length . 37.00 % for Shoot diameter . and 51.85 % for Stomata length . On the other hand this colchicine concentration causes significant decreases in the following traits value percentages 28.49 % for leaf shape factor. and 46.53 % for Stomata numbers in 1mm2 in comparisons with soacking seed in water only without colchicine . Soacking periods effects :The Soacking period of 24 hr. was significantly increased for all traits studied except leaf shape factor . and numbers of Stomata 15.66 and 13.30 % in comparison with shortest soacking period 6 hr. . Interaction effect of colchicine concentration & soacking Periods : Results Show that soacking seeds in colchicine solution 2000 mlg/l for 24 hr. was highly significant and caused reduction in values of the following traits . Leaf Shape factor 39.08 % and numbers of stomata / mm2 55.00 % . at the same time this interaction gave significant effect in the following traits : germination ratio . shoot hight . shoot diameter . stomata length and stomata width which they recorded values of 20.55 . 55.82 . 49.52 . 62.22 and 61.84 % respectively when compared with values of those seeds soaked in water only .